Pembangunan Model Database Akreditasi Online bagi Peningkatan Kerja Assesor untuk Sekolah Menengah Kejuruan - Inayatulloh, Inayatulloh (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The research aims to facilitate the implementation of the assessment of vocational school accreditation and to improve efficiency in accreditation assessment by developing a model of online information system and its database design. The assessment of vocational school accreditation covers eight aspects: content standards, process standards, competency standards, standards of educators and educational technicians, facility and infrastructure standards, management standards, financial standards and assessment standards. All activities aim to socialize the web-based information system model. It is a descriptive research method which creates a systematic and accurate description by seeking factual information on relevant agencies to detail and identifying issues or obtaining state of justification and assessments used in carrying out their duties. The result achieved is a model of information system database online accreditation for vocational high school to support the work of assessor.